A survey on chimeric UreB229-561-HpaA protein targeting Helicobacter pylori: Computational and in vitro urease activity valuation. (October 2018) - Chirani, Alireza Salimi; Ghazi, Mona; Goudarzi, Mehdi; Peerayeh, Shahin Najar; Soleimanjahi, Hoorieh; Dadashi, Masoud; Hajikhani, Bahareh
Graphical abstract: Highlights: Physicochemical evaluation of chimeric UreB229-561 -HpaA sequence from Helicobacter pylori 26695. Immunoinformatic screening of chimeric UreB229-561 -HpaA molecule. Design of the UreB229-561 -HpaA plasmid vector, in vitro expression and purification of chimeric UreB229-561 -HpaA protein. The immunological properties and rapid urease activity assessment the recombinant UreB229-561 -HpaA protein. The chimeric UreB229-561 with urease activity could act as humoral and cellular immune system activators against several strains of H.pylori . Abstract: Helicobacter pylori ( H. pylori ) as microaerophilic, Gram-negative bacterium colonize the human gastric milieu, where it impetuses chronic disorders. Vaccination is a complementary plan, along with antibiotic therapy, for clearance of H. pylori . Today, Computer based tools are essential for the evaluation, design, and experiment for novel chimeric targets for immunological administration. The purpose of this experiment was immunoinformatic analysis of UreB and HpaA molecules in a fusion arrangement and also, construction and expression of recombinant protein containing chimeric sequences. The targets sequences were screened by using of standard in silico tools and immunoinformatic web servers. The high-resolution 3D models of the protein were created and were validated; indeed, the B-and T-cell restricted epitopes were mapped on the chimeric protein. The recombinant protein in frame of the expression vector pET28a were expressed and purified successfully. The urease activity and immunoblotting were performed in vitro condition. This study confirmed that the engineered protein as a highly conserved, hydrophilic, non-allergenic contained remarkable B-cell and T-cell epitopes. It was magnificently attained; chimeric UreB229-561 -HpaA could provoke both humoral and cellular immunity. The immunoblotting was shown that the chimeric protein could be detected by serum of immunized animal and H.pylori positive patients. In this study, several antigenic patches from UreB and HpaA were identified that could be an efficient immune system activator. The in vitro analysis of our chimeric molecule confirmed its urease activity. It also confirmed that the chimeric protein could be detected by serum of immunized animal and H.pylori positive patients.